1991
DOI: 10.1088/0031-9155/36/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the value of m on the lifetime of ions in parallel-plate ionization chambers

Abstract: Measurements Concerning the collection efficiency were made for a parallel-plate ionization chamber which has a variable space between the polarizing electrode and collector. To do so. the chamber was exposed to -CO y rays at several different exposure rates and the value of m-which is equal towhere OL is the recombination coefficient, e is the charge per ion, and K, and K . are the mobilities of positive and negative ions respectively-was deduced from the collection efficiencies which were determined at vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Based on McGowan's measurements, Greening emphasized that the variations of m could occur due to the variations of both mobilities and the recombination coefficient. Takata and Matiullah (1991) have found that the value of m 2 decreases from 342 to 292 MV 2 A −1 m −1 with an increase in the applied voltage from 20 to 600 kV m −2 . They considered that this dependence was attributable to the shortened lifetime of ions in the chamber.…”
Section: From Volume To Initial Recombination and Diffusion Lossmentioning
confidence: 88%
See 1 more Smart Citation
“…Based on McGowan's measurements, Greening emphasized that the variations of m could occur due to the variations of both mobilities and the recombination coefficient. Takata and Matiullah (1991) have found that the value of m 2 decreases from 342 to 292 MV 2 A −1 m −1 with an increase in the applied voltage from 20 to 600 kV m −2 . They considered that this dependence was attributable to the shortened lifetime of ions in the chamber.…”
Section: From Volume To Initial Recombination and Diffusion Lossmentioning
confidence: 88%
“…Under such a condition the ionization current was expected to be closer to the saturation value than is predicted by expression (1), which was based entirely on recombination between positive and negative ions (Bielajew 1985). On the other hand, Niatel (1967) mentioned that the mobility depended on ion age and air humidity, and Takata and Matiullah (1991) assumed that the high electric field decreased the ion lifetime, which also reduced the ion recombination probability.…”
Section: Introductionmentioning
confidence: 92%
“…Bohm (1976) obtained a value of El for ,&rays using an extrapolation chamber. In a previous paper Takata and Matiullah (1991) used that value to correct errors in the physical parameter m measured for 6oCo y-rays. In the present work, we study initial recombination using 6oCo y-rays and examine the value of E1 for several different humidities.…”
Section: (7)mentioning
confidence: 99%
“…In addition to low experimental precision, this was ascribed to the fact that no adequate corrections for initial recombination and back-scattering losses had been made (Takata and Matiullah 1991).…”
Section: Introductionmentioning
confidence: 99%